Country of origin effect on service evaluation of foreign skilled workers in private educational institution in Malaysia / Mohamad Amiluddin Mohamed Noor - Mohamed Noor, Mohamad Amiluddin (Faculty of Business and Management, 2015)
The purpose of this research is to identify the relationship of the factors with the service evaluation of the foreign workers. There are three factors that will be analyzed the relationship which are customers’ experience, country image and customers’ ethnocentrism. These three factors will act as independent variables for the research while service evaluation of the foreign workers as a dependent variables. The research is being conducted towards students of Victoria International College Kuala Lumpur. The information is gathered by distributed of the questionnaires the students by using convenience sampling, that there are 290 students in Victoria College. By using Krejcie and Morgan chart, 165 questionnaires were distributed as a sample of the research. Their feedbacks on answering the questionnaires will be analyze and summarize by using The Statistical Package for Social Science (SPSS) version 20 and above. The results or the findings from this research revealed that customers’ experience and ethnocentrism have the significant relationship with the service evaluation of the foreign workers. Thus, several suggestions and recommendations are being made in order to increase the service of Victoria International College.